Association left ventricular lead and ventricular arrhythmias after upgrade to cardiac resynchronization therapy in patients with implantable cardioverter defibrillators. Issue 7 (13th May 2019) - Kawamura, Mitsuharu; Arai, Shuhei; Yoshikawa, Kosuke; Gokan, Toshihiko; Ogawa, Ko; Ochi, Akinori; Onishi, Yoshimi; Munetsugu, Yumi; Ito, Hiroyuki; Onuki, Tatsuya; Kobayashi, Youichi; Shinke, Toshiro
Abstract: Background: There are some controversial reports related to the pro‐arrhythmic or anti‐arrhythmic potential of cardiac resynchronization therapy (CRT) and little is known about the relationship between ventricular arrhythmia (VA) and left ventricular (LV)‐lead threshold. Hypothesis: Upgrade CRT is anti‐arrhythmic effect of VA with implantable cardioverter‐defibrillator (ICD) patients and has a relationship with the incident of VA and LV‐lead threshold. Methods: Among 384 patients with the implantation of CRT‐defibrillator (CRT‐D), 102 patients underwent an upgrade from ICD to CRT‐D. We divided patients into three groups; anti‐arrhythmic effect after upgrade (n = 22), pro‐arrhythmic effect (n = 14), and unchanging‐VA events (n = 66). The VA event was determined by device reports. We described the electrocardiography parameters, LV‐lead characteristics, and clinical outcomes. Results: Before upgrade, the numbers of VA were 305 episodes and the numbers of ICD therapy were 157 episodes. While after upgrade, the numbers of VA were 193 episodes and the number of ICD therapy were 74 episodes. Ventricular tachycardia cycle length (VT‐CL) after upgrade was significantly slower as compared to those with before upgrade. Pro‐arrhythmic group was significantly higher with delta LV‐lead threshold (after 1 month—baseline) as compared to those with anti‐arrhythmic group (0.74 vs −0.21 V). Furthermore, pro‐arrhythmic group was significantly bigger with delta VT‐CL (after 3 months—before 3 months) as compared to those with anti‐arrhythmic group ( P  = .03). Conclusions: We described upgrade‐CRT was associated with reduction of VA, ICD therapies and VT‐CL. While 14 patients had a pro‐arrhythmic effect and LV lead threshold might be associated with VA‐incidents.